Efek Penambangan Tanah Di Kawasan Perbukitan Terhadap Stabilitas Lereng dan Ancaman Bahaya Longsor - Hartono Hartono (Politeknik Negeri Semarang, 2017)
The use of land, especially settlements located in not feasible uninhabitable zones, has the potential to cause vulnerability to disasters. The occurrence of land conversion that to continuously lead to the use of space to be incompatible with the use of land, many disasters that arise due to the change of land function, uncontrolled land use change can increase the risk of landslide disaster. Landslides disaster can occur due rise to do haphazard cutting way do which makes the soil conditions become unstable causing to the slopes is getting steeper, causing the value of the safety factor to slope stability to be lower.Mining of land in Ngaliyan hill of Semarang using heavy equipment and hillside cutting due has caused the of slope conditions to be vulnerable. Mining the land what initiated by PT. IPU, in the Temple Industrial Estate has caused environmental damage that impacts, among others, the occurrence of mud floods during the rainy season arrives, the creation of critical land that caused the vulnerability of landslides. From the identification of soil conditions in the territory of housing hill BPI in location Block Q of soil testing results in the field, the type of soil in the form of clay with low carrying capacity. While the test results of soil samples in laboratory is carrying capacity lowest qu = 0.897 kg / cm2.From the stability analysis of the slopes of the safety factor to slope stability is getting smaller. So that conditions of the slopes the soil in the locations territory of hill Housing BPI become prone.From evaluation of the results of the analysis on the slope stability as the main cause due to the low value of the safety factor to the slope stability is the natural condition factor and human activity, namely the soil layer with low carrying capacity and to due excavation of soil on the side of slopes.Kata kunci : soil excavation, slope stability analysis, safety factor, mitigation